2018
DOI: 10.1002/asia.201800496
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Bonding Interactions Enable the Selective Formation of Branched Products in Palladium‐Catalyzed Allylic Substitution Reactions

Abstract: Palladium-catalyzed allylic substitution reactions have become established as an important tool for the construction of carbon-carbon and carbon-heteroatom bonds in modern organic synthesis. However, controlling the regioselectivity of this type of transformation to afford chiral branched products, in addition to controlling the enantioselectivity, is a significant challenge. Excitingly, controlling nonbonding interactions between the substituents on the π-allyl-palladium intermediate and the nucleophile or pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…Over the past few decades, palladium-catalyzed chemical transformationsh aveb een demonstrated the most effective and straightforwardm ethodologies for the constructiono f structurally diverse complicated organic molecules architectures with excellent chemoselectivities. [1] As ar esult, palladiumcatalyzed coupling approaches have become as one important research area of organometallic chemistry,w hichc an presented more elaborated poly-andheterocyclic scaffolds in pharmaceuticalc hemistry and advanced materials. [2] In particular,t he significance of palladium-catalyzed chemical transformations were fully demonstratedb yt he 2010 Nobel Price to Heck, Suzuki, and Negishif or their outstanding research works.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, palladium-catalyzed chemical transformationsh aveb een demonstrated the most effective and straightforwardm ethodologies for the constructiono f structurally diverse complicated organic molecules architectures with excellent chemoselectivities. [1] As ar esult, palladiumcatalyzed coupling approaches have become as one important research area of organometallic chemistry,w hichc an presented more elaborated poly-andheterocyclic scaffolds in pharmaceuticalc hemistry and advanced materials. [2] In particular,t he significance of palladium-catalyzed chemical transformations were fully demonstratedb yt he 2010 Nobel Price to Heck, Suzuki, and Negishif or their outstanding research works.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the formation of the linear products is predominant in most cases since the nucleophilic attack at the less hindered, terminal carbon is favored over the internal carbon center. Previous studies have revealed that the regioselectivity of an outer‐sphere pathway can be controlled to a certain extent through a rational design of the allylic substitution process (i.e., substrate, ligand and additive) . For instance, Trost and co‐workers developed a palladium‐catalyzed branched selective allylic amination of vinyl epoxides, in which a hydrogen‐bonding interaction between the nucleophile and the oxygen anion of the π‐allyl‐palladium intermediate was proposed to be crucial in guiding the regioselectivity towards the formation of the branched product …”
Section: Introductionmentioning
confidence: 99%
“…The resulting Pd‐containing 1,4‐dipolar species A would react with deconjugated butenolide substrate 2 through an asymmetric allylic substitution, and C would be delivered in a regio‐ and stereocontrolled manner together with the regeneration of the chiral Pd 0 catalyst. In this step, inspired by research on AOC where the hydrogen bonding between Lewis base catalysts and substrates was responsible for the unusual α‐selectivity, we planned to use similar nonbonding interactions between the Pd‐containing dipoles and enolates (see B in Scheme d) to control both the branched selectivity of allylic substitution and the α‐selectivity of the deconjugated butenolide. Finally, significant dihydroquinol‐2‐one products ( 3 ) would be obtained after the subsequent intramolecular aminolysis process…”
Section: Methodsmentioning
confidence: 99%
“…[13] As depicted in Scheme 1d,w ee nvisioned that the chiral Pd 0 catalyst, formed from aPd 0 precursor and achiral P, S-ligand, would undergo an oxidative addition to the vinyl carbamate substrate 1.The resulting Pd-containing 1,4-dipolar species A would react with deconjugated butenolide substrate 2 through an asymmetric allylic substitution, and C would be delivered in ar egio-and stereocontrolled manner together with the regeneration of the chiral Pd 0 catalyst. In this step,inspired by research on AOCw here the hydrogen bonding between Lewis base catalysts and substrates was responsible for the unusual a-selectivity, [6] we planned to use similar nonbonding interactions between the Pd-containing dipoles and enolates (see B in Scheme 1d)tocontrol both the branched selectivity of allylic substitution [14] and the a-selectivity of the deconjugated butenolide.F inally,s ignificant dihydroquinol-2-one products (3)w ould be obtained after the subsequent intramolecular aminolysis process. [15] Given the importance of chiral ligands for the reaction efficiency and enantioselectivity,t his study began with the evaluation of our chiral hybrid P, S-ligands for cycloaddition between the the vinyl carbamate 1a and deconjugated butenolide 2a (Table 1).…”
mentioning
confidence: 99%